The Contribution of Parents Attention to Student Achievement Motivation - Nofrizal Nofrizal; Herman Nirwana; Alizamar Alizamar (Global Econedu, 2020)
The low student achievement motivation is something that must be considered. Parents attention became one of the factors that can influence student achievement motivation. The purpose of this study to describe the contribution of parent attention to student’s achievement motivation in SMK Muhammadiyah 1 Padang. This research uses regression analysis. In the research took the sample of 233 students by using purposive sampling technique. It was used instrument